The morals of the market: human rights and the rise of neoliberalism - Whyte, Jessica (Verso, 2019)
Drawing on detailed archival research on the parallel histories of human rights and neoliberalism, Jessica Whyte uncovers the place of human rights in neoliberal attempts to develop a moral framework for a market society. In the wake of the Second World War, neoliberals saw demands for new rights to social welfare and self-determination as threats to “civilisation”. Yet, rather than rejecting rights, they developed a distinctive account of human rights as tools to depoliticise civil society, protect private investments and shape liberal subjects.